2019
DOI: 10.1177/0748730419861765
|View full text |Cite
|
Sign up to set email alerts
|

Disassortative Network Structure Improves the Synchronization between Neurons in the Suprachiasmatic Nucleus

Abstract: In mammals, an endogenous clock located in the suprachiasmatic nucleus (SCN) of the brain regulates the circadian rhythms of physiological and behavioral activities. The SCN is composed of about 20,000 neurons that are autonomous oscillators with nonidentical intrinsic periods ranging from 22 h to 28 h. These neurons are coupled through neurotransmitters and synchronized to form a network, which produces a robust circadian rhythm of a uniform period. The neurons, which are the nodes in the network, are known t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…In neuronal networks, disassortativity has been proposed to improve network stability 72 which may indicate reduced sensitivity to weak stimuli 73 . Interestingly, disassortative neural networks have also been linked to increased synchronisation of activity 74 . Network level relationships have not been previously explored among astrocytes in situ and it is too early to say whether changes that we observed here warrant similar conclusions with regard to stimulus sensitivity, synchronisability, etc.…”
Section: Discussionsupporting
confidence: 54%
“…In neuronal networks, disassortativity has been proposed to improve network stability 72 which may indicate reduced sensitivity to weak stimuli 73 . Interestingly, disassortative neural networks have also been linked to increased synchronisation of activity 74 . Network level relationships have not been previously explored among astrocytes in situ and it is too early to say whether changes that we observed here warrant similar conclusions with regard to stimulus sensitivity, synchronisability, etc.…”
Section: Discussionsupporting
confidence: 54%
“…It was found that the incoming degree is similar for most SCN neurons but the outgoing degree varies between SCN neurons and the nodes with large outgoing degree are located in the core (McBride and Petzold, 2018). We found that the SCN network for each slice partially is a scale-free network (Gu et al, 2019a). A power-law distribution of the node degrees was found, as well as a short averaged path length (around 2.5).…”
Section: Properties In Directed Scn Networkmentioning
confidence: 67%
“…In order to explore the directed network structure of the SCN, two articles performed an analysis on the data from Ref. (Abel et al, 2017) using the method of information theory based technique (McBride and Petzold, 2018) and the method of the transfer entropy (Gu et al, 2019a). It was found that the incoming degree is similar for most SCN neurons but the outgoing degree varies between SCN neurons and the nodes with large outgoing degree are located in the core (McBride and Petzold, 2018).…”
Section: Properties In Directed Scn Networkmentioning
confidence: 99%
See 2 more Smart Citations